Mechanical and structural assessment of laboratory- and field-compacted asphalt mixtures - Airey, G.D.; Collop, A.C. (Taylor & Francis, 2014)
Compaction forms an integral part in the formation of the aggregate orientation and structure of an asphalt mixture and therefore has a profound influence on its final volumetric and mechanical performance. This article describes the influence of various forms of laboratory (gyratory, vibratory and slab-roller) and field compaction on the internal structure of asphalt specimens and subsequently on their mechanical properties, particularly stiffness and permanent deformation. A 2D image capturing and image analysis system has been used together with alternative specimen sizes and orientations to quantify the internal aggregate structure (orientation and segregation) for a range of typically used continuously graded asphalt mixtures. The results show that in terms of aggregate orientation, slab-compacted specimens tend to mimic field compaction better than gyratory and vibratory compaction. The mechanical properties of slab-compacted specimens also tend to be closer to that of field cores. However, the results also show that through careful selection of specimen size, specimen orientation and compaction variables, even mould-based compaction methods can be utilised with particular asphalt mixtures to represent field-compacted asphalt mixtures.